1992
DOI: 10.1152/ajplung.1992.262.3.l313
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of alveolar type II cell differentiation in fetal rhesus monkey lung by administration of EGF

Abstract: To examine the effect of epidermal growth factor (EGF) on lung parenchymal maturation in fetal rhesus monkey, recombinant human EGF was administered intraperitoneally (IP) at 66 mg/kg body wt over a 7-day period into the fetal peritoneal cavity alone or IP and into the amniotic fluid (AF) simultaneously. The saline carrier was injected IP and AF into control (CO) fetuses. The body weights of the IP + AF group were significantly larger than CO. Overall lung growth, measured as wet lung weight or fixed volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 0 publications
2
48
1
Order By: Relevance
“…Their prominent localization in airway epithelium suggests a possible role in airway growth and epithelial cell differentiation and maturation. Many studies of pharmacologic treatment of developing lung with EGF have demonstrated potent effects on branching morphogenesis (14,20,21) and lung epithelial cell maturation (22)(23)(24)(25). Taken together, these studies indicate that EGF can exert effects on both lung morphogenesis and functional maturation of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their prominent localization in airway epithelium suggests a possible role in airway growth and epithelial cell differentiation and maturation. Many studies of pharmacologic treatment of developing lung with EGF have demonstrated potent effects on branching morphogenesis (14,20,21) and lung epithelial cell maturation (22)(23)(24)(25). Taken together, these studies indicate that EGF can exert effects on both lung morphogenesis and functional maturation of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Also, inhibition of endogenous EGF production with an antisense oligonucleotide directed against EGF in fetal mouse lung explants reduced airway branching (21). Pharmacologic treatment of fetal rat, monkey, rabbit, and sheep lungs at various gestational ages with EGF results in accelerated type I1 cell differentiation, DNA synthesis, and surfactant production (22)(23)(24)(25).…”
Section: Strandjord Et Almentioning
confidence: 99%
“…All of them are mitogens in type II pneumocytes, and act synergistically to mediate their maturation and increase surfactant synthesis [8]. EGF had benefi cial eff ects in an animal model of ALI [39], and inhibition of EGF receptor had a detrimental eff ect during airway epithelium repair [40]. KGF has been linked to upregulation of anti-infl am matory cytokines and modulation of epithelial cell migration [41].…”
Section: Therapeutic Strategies Aimed At Lung Repairmentioning
confidence: 99%
“…We conclude that prenatal exposure to EGF stimulates biochemical and histologic maturation of the lung and markedly attenuates the clinical severity of respiratory disease in this model of simian respiratory distress syndrome. (1)(2)(3)(4)(5). EGF induces increased synthesis and secretion of surfactant and surfactant-associated proteins in these cells.…”
mentioning
confidence: 99%